Personal Branding Strategies Of The Deputy Mayor Of Surabaya Through The Instagram Account @Cakj1 - Nanda Alya Karlina Amini; Irwan Dwi Arianto (Eduvest - Journal of Universal Studies, 2024)
Competition is becoming tougher, and the easy and fast use of social media has made people more dependent on it. The ease of accessing Instagram social media has made Cak Ji, the Deputy Mayor of Surabaya. He routinely documents his daily activities through photos and videos and uploads them to his personal Instagram account. Researchers seek to analyze the video and photo content uploaded by the individual on their Instagram account, from February 26, 2021, to February 26, 2022. The aim is to determine whether the image displayed is in line with the actual personality or merely a portrayal done to meet content needs on the platform. This study uses the concept of personal branding, particularly through the application of The Eight Laws Of Personal Branding developed. The research method used is qualitative research with a descriptive qualitative approach. In collecting data, the method used is documentation. Data analysis uses the model of data reduction, data presentation stage, and conclusion drawing or verification stage, by interpreting and analyzing the existing data based on the theory used by researchers to draw conclusions. From the research conducted on the Instagram account @Cakj1, it can be shown that Cak Ji's personal branding fulfills the eight main concepts of personal branding by Peter Montonya, namely: 1. (The Law of Specialization), 2.(The Law of Leadership), 3. (The Law of Personality), 4. (The Law of Distinctiveness), 5.(The Law of Visibility), 6. (The Law of Unity), 7. (The Law of Persistence), 8. (The Law of Goodwill).